Interventions to Improve Nurse Therapeutic Communications in the Context of Palliative Care: Literature Review - Pangkey Jelly; Erna Rochmawati (STIKep PPNI Jawa Barat, 2022)
Aims: The aim of this research is to obtain evidence of what research has been done and to know the effect of the training. Methods: Through a review using 3 databases, namely Ebsco, ScienceDirect, PubMed, and other sources with the keywords “nurse; communication skills; training; palliative care”. From 2001 to 2021, the type of research consisted of RCT, experiment, randomization of pre-test – post-test, randomized trial, implementation, and curriculum development. Results: Obtained a review of 7 articles in this study from 495 results found from several pieces of training carried out including psychological training, workshops, module preparation, role play or simulations, and audio-visual training. In general, the direct effect of communication training on nurses can increase communication competence, while in patients it affects the quality of life, patient satisfaction increases, and symptoms of psychological distress in patients can decrease. Conclusions: Communication training for nurses is very important. To improve nurses' communication skills, it is expected that self-development through various other types of research to increase competence so that it can be applied to nursing services.